Mycorrhizal formation by Paxillus involutus strains in relation to their IAA-synthesizing activity - Rudawska, M L (The New phytologist, 1997)
IAA production by the ectomycorrhizal fungus Paxillus invotutus grown in pure culture was investigated by testing IAA accumulation or IAA-synthesizing activity. All the Paxillus involutus strains studied released indole compounds either when incubated with 0.5 mM tryptophan or in its absence. HPLC analyses of indole compounds all yielded two main peaks identified by reference to controls as being IAA and indole-3-carboxylic acid and a small peak of indole-3-aldehyde. Mass spectrometry unequivocally confirmed IAA production in the culture filtrates and in the incubation solution used to study in vitro IAA-synthesizing activity. The IAA-synthesizing activity was found to vary widely, from 7.6 to 137.4 nmol IAA h-1 g-1 f. wt, between strains. The mycorrhizal activity of these strains with seedlings of Pinus sylvestris cultured under aseptic conditions was tested. Fungal strains that were characterized in pure culture conditions by high LAA-synthesizing activity induced more fine roots and significantly higher numbers of mycorrhizas than strains which showed a low activity of IAA synthesizing enzymes. The increased ectomycarrhiza formation was generally accompanied by an increased growth of seedlings